Pengaruh Penggunaan Sirip Aksial Pada Alat Penukar Kalor Pipa Ganda Terhadap Proses Pelelehan Dan Pembekuan Parafin Sebagai Penyimpan Energi Thermal - Mahyudi, Erik Tri (Universitas Muhammadiyah Metro, 2024)
This research aims to analyze the effect of fin geometry on the thermal performance of the latent heat energy storage and release system of axially finned horizontal tubes with variations in the number and height of fins. The research results show that increasing the number of axial fins by 4.6% and 13.7% of the total volume reduces melting time by 6.9% and 16.1% and 1.3% and 1.8% in the freezing process. Increasing the fin height by 11.1% and 24.3% of the total volume reduces the melting time by 2.7% and -2.7% and 0.9% and 3% in the freezing process. The benefits of increasing the number and height of fins are evaluated to optimal limits for the thermal energy storage and release system.